Continuous-grouped-self-learning: in the perspective of lecturers, tutors and laboratory instructors - Mohd Azau, Mohd Azrin; Low, Ming Yao; Goo, Soon Aik; Chin, Kock Yeong; Nor, Mohamad Nizam; Abdullah, Ahmad Yusri; Mohamad Jamil, Mohd Hafidz; Yahya, Nasiruddin; Abas, Ahmad Fauzi; Saripan, M. Iqbal (Canadian Center of Science and Education, 2009)
This paper presents the perception of lecturers, tutors and lab instructors towards the implemented Continuous-Group-Self-Learning (CGSL) in the Department of Computer and Communication System Engineering (CCSE), Universiti Putra Malaysia. This innovative system introduces mock teaching and student-lecturer role as a technique of delivery. The system ensures a continuous group work and the students are learning with class-oriented problem-based learning (CO-PBL) instead of seasonal project oriented problem-based learning (PO-PBL). The radical change in the assessment by adopting mock teaching oriented assessment (MTOA) has given a new definition to assess the student thoroughly. 49 respondents have taken part in this study, in which 30 of them are lecturers, 8 are tutors and 11 are laboratory instructors who currently active serving in the department. In general, 56% of the respondent do not agree this learning system shifted the teaching job to the students and 56.55% of them disagree this approach is a burdensome to the students who are undergoing this learning style. This system in fact a catalyst that urges the lecturers, tutors and lab instructors to enhance themselves in order to cope up with the ‘knowledge demand’ from the student when 82.1% of the respondents agree to be more knowledgeable as compared to conventional teaching method.